Implementasi Pendidikan Multikultural Untuk Meningkatkan Keharmonisan Dalam Keberagaman - Ridwan, Mohammad; Saputra, Edy; Hidayat, Rahmat; Harahap, Sumper Mulia (Bayani, 2024)
The aim of this study is to analyze the role and implementation of multicultural education in shaping students' character to live harmoniously in the midst of diversity. The method used is a literature review with both theoretical and practical approaches to the multicultural education models applied in various countries. The results of the study indicate that multicultural education has a significant impact in reducing prejudice, increasing empathy, and developing the social skills necessary in a pluralistic society. A curriculum that integrates multicultural values, teacher training that is sensitive to diversity, and the use of participatory teaching methods have proven to be effective in creating an inclusive learning environment. Based on the findings, the recommendations proposed include the need for enhanced teacher training on cultural diversity, the development of a more adaptive curriculum to multicultural values, and the provision of more adequate resources to support the implementation of multicultural education in schools.